Research Roundup. Issue 12 (December 2015) - Unknown
Abstract : DHA study finds no effect on PTSD symptoms after injury Extended‐release guanfacine effective for youths with autism Retrospective study of varenicline finds no evidence of adverse risk Adjunctive quetiapine may improve outcomes in PMDD treatment Tricyclic antidepressants associated with recurrence of stroke Cognition not altered in postmenopausal women on hormones